Igor Stravinsky and Aldous Huxley: portrait of a friendship - Outhier, Sara Diane (Kansas State University, 2009)
Igor Stravinsky and Aldous Huxley maintained a sincere and abiding friendship for nearly two decades while both men were living in Los Angeles, California. Huxley’s command of music literature and understanding of musical concepts promoted a vital exchange of ideas between the two men. By the time of their meeting in Hollywood, each man appreciated the importance of the other in his field of expertise, despite Huxley’s negative criticisms of Stravinsky’s music in the 1920s. This mutual respect led to collaborations between Stravinsky, Huxley, and the American conductor Robert Craft on a series of concert-lectures and recordings. Stravinsky esteemed his friend so highly that he was compelled to dedicate a composition that he had been writing at the time of Huxley’s death to the writer’s memory. This paper includes a chapter of biographical information on Aldous Huxley, a chapter detailing the friendship of Stravinsky and Huxley in chronological order, a chapter about Huxley’s criticisms of Stravinsky’s music, a chapter about Huxley’s concert collaborations with Stravinsky and Craft, and a chapter detailing the compositional history and techniques of Stravinsky’s Variations for Orchestra (in Memory of Aldous Huxley). The first appendix lists additional meetings between Stravinsky and Huxley, as detailed in the writings of Igor Stravinsky, Vera Stravinsky, and Robert Craft. The second appendix is a chronological list of all Huxley writings mentioning Stravinsky.
Keywords: Igor Stravinsky; Aldous Huxley; Variations (in Memory of Aldous Huxley); Weekly Westminster Gazette; Music (0413)